Double Whammy: Monoclonal Gammopathy Induced ANCA-associate Glomerulonephritis - Magbri, Awad; El-Magbri, Mariam; Rges, Huda; Hermiz, Joshua; Hernandez, Abrego (British Journal of Healthcare and Medical Research, 2024)
ANCA-associated vasculitis (AAV) is an inflammatory condition affecting small blood vessels, characterized by necrosis of glomeruli in the kidneys. It is driven by an autoimmune response in which anti-neutrophil cytoplasmic antibodies (ANCAs) target proteins in neutrophils, primarily myeloperoxidase (MPO) and proteinase 3 (PR3) (1). This autoimmune reaction leads to neutrophil activation and degranulation, causing vascular endothelial damage (2). Monoclonal gammopathy (MG) involves the clonal proliferation of plasma cells or B-lymphocytes, producing a monoclonal immunoglobulin (M-protein). MG can range from benign conditions, such as monoclonal gammopathy of undetermined significance (MGUS), to malignant disorders like multiple myeloma (MM) and Waldenström’s macroglobulinemia (WM). The presence of MG can result in the deposition of abnormal proteins in various organs, including the kidneys, potentially inducing an autoimmune response and leading to AAV. While the exact mechanism remains unclear, it is hypothesized that these abnormal proteins may trigger immune responses that result in ANCA production and subsequent glomerular inflammation.